Sustainability Accounting: Nilai Perusahaan Dan Carbon Emission Disclosure - Apriliani, Lina; Kadir, Kadir; Hifni, Syaiful (Universitas Gorontalo, 2024)
The aim of this research is to test the correlation between carbon emission disclosure and firm value. Employing multiple linear regression analysis on energy sector companies listed on the Indonesia Stock Exchange from 2018 to 2021, this study utilized a sample of 51 energy sector companies selected through purposive sampling methods. The findings of this research demonstrate strong evidence of a negative correlation between carbon emission disclosure and firm value. The research results also indicate that size and leverage significantly influence firm value, while profitability does not affect firm value. This study highlights the significance of carbon emission disclosure on firm value. The implications of these findings emphasize the importance of encouraging companies to be more proactive in disclosing and managing carbon emissions as a strategy to gain investor trust and support and maintain long-term value.